Biochemistry, pharmacology and physiological role of sex hormone binding globulin - KOURETAS (Δ. ΚΟΥΡΕΤΑΣ) D.; LALIOTIS (Β. ΛΑΛΙΩΤΗΣ) V.; ANTONOGLOU (Ο. ΑΝΤΩΝΟΓΛΟΥ) O. (Journal of the Hellenic Veterinary Medical Society, 2018)
Sex steroid binding protein (SBP) is a plasma protein that specifically binds sex steroids with high affinity. It is synthesized in the liver and circulates in the plasma of many species including human, monkey, cattle, dog, cat and others. SBP is a dimeric protein with a Mr ranging between 84-9Θ KDa and binds one steroid molecule per dimer. Its expression is regulated by many hormones and estradiol promotes while testosterone inhibits its expression. Its physiological role is not known completely, but it is likely to control at least the bioavailable levels of circulating steroids. Experimental evidence from our laboratory and others supports the dogma that non-bound steroids are free to enter the target cells and act. After the discovery of SBP-membrane receptor, it seems that SBP serves also other biological role except that of binding steroids. All recent reports are discussed.